REPRESENTASI PERAN KAKAK SEBAGAI PENGGANTI ORANG TUA DALAM NOVEL DIA ADALAH KAKAKKU KARYA TERE LIYE: KAJIAN SOSIOLOGI SASTRA PERSPEKTIF SOERJONO SOEKANTO - Nur Afika Sri Lestari; Elsa Mulya Karlina (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2026)
This study aims to analyze the role of an older sibling as a substitute parent in the novel Dia Adalah Kakakku by Tere Liye using a sociological literary approach based on Soerjono Soekanto’s role theory. The focus of this research is the representation of the older sibling’s role in performing parental functions, including protection, affection, guidance, economic responsibility, and self-sacrifice for the younger sibling. This study employs a qualitative method with a library research design. The primary data source is the novel Dia Adalah Kakakku, while secondary data are obtained from books, journals, and other relevant literature. Data collection techniques include intensive reading and note-taking, which are then analyzed using content analysis. The results of the study show that the older sibling in the novel assumes the role of a substitute parent due to the absence or inability of biological parents to fulfill their parenting functions. This role is reflected in various actions such as providing protection, emotional support, moral guidance, fulfilling daily needs, and sacrificing personal interests for the future of the younger sibling. These findings indicate that family roles are dynamic and can shift according to social conditions, as represented in literary works.